Pengujian Resiko Redenominasi terhadap Nilai Tukar Rupiah - Abdul Holik (Politeknik Ganesha Medan, 2021)
The redenomination is a breakthrough policy to induce stabilization because making transactions easier among the economic agents. This quantitative research aims to find the properness of the redenomination policy in Indonesia. The focus of this research is to analyze the impact of redenomination risk on rupiah exchange rate performance. It is conducted from April 1st, 2015 until May 9th, 2016. The method of analysis used here is VECM (Vector Error Correction Model) to find relation reciprocally among the three variables: CDS (Credit Default Swap) as a proxy for redenomination risk, exchange rate, and sovereign yields. Based on the result, we find that there are negative impacts in the long-run and short-run from redenomination risk on the rupiah exchange rate. Meanwhile, the sovereign yield has a positive impact on the rupiah exchange rate in the long run. In the short run, the exchange rate has a positive impact on redenomination, as well as on sovereign yield. The sovereign yield also has a positive effect on the exchange rate, as well as on the redenomination risk. But there is no impact of redenomination risk on the sovereign yield. From this finding, we should suggest that redenomination is a not proper decision yet. It is because the weakness of rupiah after its implementation due to sentiment of over-confidence among the economic agents sometimes triggers uncontrollable and high inflation rate. For the successful policy, previously the government should take action to reduce the inflation rate.